1993
DOI: 10.1007/bf00021526
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of tomato (Lycopersicon esculentum L.) genes encoding shikimate pathway isoenzymes. II. Chorismate synthase

Abstract: In tomato (Lycopersicon esculentum L. cv. UC82b) two distinct genes (designated LeCS1 and LeCS2) code for chorismate synthase. The corresponding cDNAs have been isolated and characterized. The deduced amino acid sequences are 88% identical. Both genes encode chorismate synthases with putative plastid-specific N-terminal transit peptides. The two genes are predominantly expressed in flowers and roots and, to a lesser extent, in stems, leaves, and cotyledons, but the steady-state levels of LeCS1-specific transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Besides DAHP synthase and AS, CS is the third enzyme of the shikimate pathway known to be encoded by two distinct genes which respond differentially to pathogen-derived stress factors. The differential expression of the two tomato CS genes in response to elicitor was not expected in this case, since both genes exhibit the same organ-specific expression pattern (14,21). In this respect the two CS genes clearly differ from the two DAHP synthase genes of tomato.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Besides DAHP synthase and AS, CS is the third enzyme of the shikimate pathway known to be encoded by two distinct genes which respond differentially to pathogen-derived stress factors. The differential expression of the two tomato CS genes in response to elicitor was not expected in this case, since both genes exhibit the same organ-specific expression pattern (14,21). In this respect the two CS genes clearly differ from the two DAHP synthase genes of tomato.…”
Section: Resultsmentioning
confidence: 77%
“…It was previously shown that Pmg induces PAL activity and ethylene biosynthesis in tomato cells (10,16) and, furthermore, that the induction of PAL activity by YIE was independent of ethylene biosynthesis (17). Of (18,19,21). To link the expression patterns of these genes with those of the general phenylpropanoid pathway, the expression of the PAL gene family was also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Very recent studies on the organ-specific expression of genes encoding SK pathway isoenzymes in green and nongreen tissues (Eberhard et al, 1993;Gorlach et al, 1993a, 199310) suggest an organ-specific regulation of AAA synthesis. Of interest is the elevated transcription of genes of SK pathway enzymes in nongreen parts (Gorlach et al, 1994). Such elevated transcription could mean an intensive synthesis in these parts and an export of surplus prearomatic and aromatic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, native gradient (8-25%) gel electrophoresis of matCS (Fig. 5) conserved among all known CSs (Gorlach et al, 1993), deleterious consequences upon enzyme activity due to relatively large additions adjacent to this region are not surprising. At the plant level, we would conclude from these data that activity of plant CS, as defined by our assay conditions, is dependent on import into plastids.…”
Section: Complementation Of E Coli Cs Mutant Ab2849mentioning
confidence: 99%